2012
DOI: 10.1002/pbc.24258
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low‐dose involved‐field radiation therapy on pediatric patients with lymphocyte‐predominant Hodgkin lymphoma treated with chemotherapy: A report from the Children's Oncology Group

Abstract: Background Treatment of pediatric lymphocyte-predominant Hodgkin lymphoma (LPHL) is controversial but has typically consisted of both chemotherapy and radiation. Radiation therapy is associated with potential late effects in children and adolescents. We examined the impact of radiation therapy on long-term outcome of patients with LPHL treated on CCG-5942, a large pediatric cooperative group study of Hodgkin lymphoma. Procedure Eighty-two patients with LPHL were registered on CCG-5942. Fifty-two patients (63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 49 publications
1
24
0
3
Order By: Relevance
“…Among early‐stage patients with LPHL, COG AHOD03P1 demonstrated that 75% of stage IA patients can avoid chemotherapy after complete surgical resection alone and >90% can avoid IFRT while maintaining excellent outcomes when treated with three cycles of doxorubicin, vincristine, prednisone, and cyclophosphamide (AV‐PC) . The impact of low‐dose IFRT on patients with LPHL was evaluated previously on study CCG‐5942 . On this protocol, intermediate‐risk (group 2) patients (including stage I with adverse disease features, stage II with adverse disease features, and/or with clinical B symptoms, and stage III) received 6 cycles of cyclophosphamide, vincristine, prednisone, procarbazine, doxorubicin, bleomycin, and vinblastine (COPP/ABV) and were then randomized to IFRT or no further treatment if they achieved a CR .…”
Section: Discussionmentioning
confidence: 99%
“…Among early‐stage patients with LPHL, COG AHOD03P1 demonstrated that 75% of stage IA patients can avoid chemotherapy after complete surgical resection alone and >90% can avoid IFRT while maintaining excellent outcomes when treated with three cycles of doxorubicin, vincristine, prednisone, and cyclophosphamide (AV‐PC) . The impact of low‐dose IFRT on patients with LPHL was evaluated previously on study CCG‐5942 . On this protocol, intermediate‐risk (group 2) patients (including stage I with adverse disease features, stage II with adverse disease features, and/or with clinical B symptoms, and stage III) received 6 cycles of cyclophosphamide, vincristine, prednisone, procarbazine, doxorubicin, bleomycin, and vinblastine (COPP/ABV) and were then randomized to IFRT or no further treatment if they achieved a CR .…”
Section: Discussionmentioning
confidence: 99%
“…In the past 15 years, studies in pediatric NLPHL (including a large recent prospective North American study) have focused on decreasing treatment in early stage NLPHL. Excellent overall survivals have been reported with complete nodal excision of Stage IA (especially when only a single node was involved), involved field radiotherapy alone in Stage IA disease, or lower intensity chemotherapy in early stage unresectable disease . Relapses in NLPHL have been found amenable to salvage chemotherapy, hence the trend toward decreasing the intensity of frontline therapy to minimize the risk of treatment toxicity and late effects .…”
Section: Discussionmentioning
confidence: 99%
“…This is very encouraging and assuages concerns of widespread disease at relapse after surgery as the sole treatment. Moreover, the first line surgery alone approach will spare around 70–80% of patients the chemotherapy‐related acute and late toxicity without compromising cure rates in the 20–30% of patients who will relapse with this treatment strategy (Mauz‐Körholz et al , ; Appel et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Although excision lymph node biopsy as primary treatment in selected stage IA patients is a reasonable treatment option (Pellegrino et al, 2003;Mauz-K€ orholz et al, 2007;Appel et al, 2012;Shankar et al, 2012), a minority will relapse, mainly those who had incomplete resection. However, salvage after relapse appears to be relatively straight forward, as is shown in this retrospective report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation